Relationship between Housing Condition, Soldiers' Social Life and Morale in Coral Barracks, Nigeria - Maiyaki, Sani Audu; Ishiyaku, Bala; Yunusa, Muhammed Hayatu; Ibrahim, Aisha; Milala, Sani Inusa (Journal of Technology Management and Business, 2021)
Despite the numerous empirical studies that have been conducted on housing conditions, there is still very little research work carried out on military barracks life, the impact of the condition of the barracks' accommodation on the soldiers' social life and morale. Thus, this paper presents a study on the relationship between housing conditions, soldiers' social life, and morale in Coral Barracks Nigeria and covers only the non-commissioned officers' quarters. A quantitative method using a questionnaire survey was used with a sample size of 260. The data were analysed using descriptive statistics as well as parametric measurements. A total number of 194 questionnaires retrieved from the respondents were used in the analyses. Building services attributes had a strong and significant positive correlation. Moreover, neighbourhood and soldiers' life correlate significantly, negative but weak, while physical housing attributes and neighbourhood attributes correlate significantly but negatively and weak with children's life. Neighbourhood attributes and soldiers' morale recorded a significant, negative but weak correlation. In light of these findings, this study recommends that a standard strategic plan for efficient barrack housing construction, management, and maintenance is designed.